Sharing to Carring: Self Regulated Millennials Facing Tuition Loads - Mega Ristanti; Dina Rahmawati; Mawardi Djamaluddin (Archipelago, 2021)
Most students are in Online learning has psychological problems, amongothers: stress due to many tasks, adjustments self that less burden thought thatGreat, and there is Powerlessness in the student. Therefore, there needs to bepsychological support so that students can be optimistic, realistic, hopeful,and achieve the desired target during the learning process. The purpose of thisdevotional activity is to give information steps backing psychological tostudents so that students can undergo learning daring with good. Audiencesgoal In this activity, there are as many students as 62 participants, using lecturemethods, Q&A, and discussions conducted online using the application zoom.Result implementation Devotion The society shows that nearly 50 percent ofstudents understand the concept of psychological support information duringlearning well.Keyword: self regulated, tuition loads